SIX YEARS OF FINANCIAL ACCOUNTING RESEARCH IN INDONESIA - Rijal, Ikmalur; Rakhman, Anita; Fatmanah, Yiska; Lailatus Sofia, Mega; Dwi Nafrida, Safa; Rahmawati S, Lusy (Riviera Publishing, 2023)
This study describes the development of financial accounting research in Indonesia, consisting of 9 nationally accredited journals in Indonesia. The sample obtained from 2017 to 2022 obtained 58 articles discussing financial accounting. Based on the analysis results, most research on financial accounting in Indonesia was published in JAB at 17%. In comparison, JRAP and e_JRA were 13% each. Of the 58 articles obtained, 14 were qualitative methods research, while research using quantitative methods was 44. In qualitative research, the most widely used method is descriptive analysis. In contrast, the most widely used method in quantitative research is multiple linear regression. This research provides historical evidence of the development of research on financial accounting in Indonesia so that it can be a literature review material for future research that will conduct the same research in Indonesia.